Quantificação da distribuição celular em imagens de culturas primárias de gânglio da raiz dorsal em interface com matrizes multieletrodo - Neves, Amanda Ferreira (2012)
This work aims to quantify and characterize the neuron-microelectrode interface of dorsal-root ganglion primary cultures plated on multi-electrode arrays (MEA), in order to establish culture conditions that will enhance neuronal activity recordings. Quantitative analysis of cellular distribution was performed using images obtained by confocal microscopy, in order to compute a map of the distances between neurons and microelectrodes. The direct and indirect topological evolution of cultures plated on MEA devices were also analyzed, during three days in vitro, and compared with cultures plated on common cell culture dishes. Results point out that the proportion of adhered neurons on MEA dishes was similar to that on common dishes, remaining unchanged throughout the three days in vitro. The mean distance between neuron and microelectrode, for each dish type, was also similar. Thus, the best culture conditions could be summarized as follows: to increase the number of plated neurons, decrease the neuron-microelectrode distance and reduce neuronal loss, making possible to improve the contact with neurons and microelectrodes. Finally, this quantitative analysis provides a simple description of the culture attached to the MEA, so that to characterize the neuron-microelectrode interface and also to allow further insights on electrical activity recordings.